Experimental research on innovative design of intangible cultural heritage products based on UCD and cultural gene theory - Huang, Tingting; Abdullah, Muhammad Fadhil Wong Bin; Zalay @ Zali, Abdul Aziz Bin (Edelweiss Applied Science and Technology, 2024)
This study aims to explore how to achieve innovative design for intangible cultural heritage (ICH) tourism products through User-Centered Design (UCD) theory and the cultural gene approach. Using the national ICH of Mianzhu New Year Pictures as a case study, the research, guided by UCD theory, conducts an in-depth analysis of user needs, with a detailed investigation into users’ aesthetic preferences and functional requirements to ensure that the design meets modern market demands. Additionally, the cultural gene approach provides theoretical support for extracting and transforming the core cultural symbols of Mianzhu New Year Pictures, allowing these symbols to be effectively integrated into contemporary products through symbolic design. This approach ensures that the design retains the cultural characteristics of Mianzhu New Year Pictures while enhancing users’ cultural identity and overall experience. This study employs a mixed research methodology, with a primary focus on design experimentation, supported by KANO-AHP, ethnographic fieldwork, and iterative testing to analyze user needs and optimize the product. Initially, KANO-AHP is used to conduct a quantitative analysis of user requirements, identifying priorities in functionality, aesthetics, and emotional appeal to provide precise guidelines for product design. Next, ethnographic fieldwork is conducted through observation and interviews to gain deep insights into the cultural background, artistic features, and user contexts of intangible cultural heritage, enabling the extraction of representative cultural gene elements. Finally, the study employs design experimentation for multiple rounds of user testing and product iteration, incorporating feedback from focus groups to progressively enhance the product’s functionality and aesthetic appeal, thereby increasing practicality and user satisfaction. This comprehensive experimental approach allows the researcher to dynamically adjust the product based on real-time feedback, ensuring continuous improvement in actual applications while effectively integrating cultural heritage with modern user needs. The results of the study show that the combination of UCD and cultural genetics methodology can effectively enhance the market attractiveness and cultural heritage value of NRM products. This study not only promotes the application of UCD and cultural gene method in the design of non-heritage products and provides practical guidance for the modernisation and innovation of non-heritage products, but also opens up a new way of thinking for the inheritance and development of non-heritage culture in modern society.